Hybrid-modulation-based control technique for reduction of output voltage ripples in frequency-modulated switch-mode power converters - Deniss Stepins; Jin Huang; Janis Audze (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In this paper a novel control technique for switching-frequency-modulated switch-mode power converters (SMPC) operating in discontinuous conduction mode is proposed. The use of the technique leads to significant reduction in peak-to-peak output voltage and peak currents increased due to straightforward application of switching frequency modulation (SFM). The technique is based on hybrid modulation scheme in which both switching frequency and duty ratio are modulated simultaneously by the same modulation signal. Theoretical analysis and experimental verification of the proposed technique are presented in details. Both computer simulations and experiments show that switching-frequency-modulated SMPC with the proposed control technique in comparison to SMPC without SFM has appreaciably lower conducted electromagnetic emissions, at the cost of slightly increased peak-to-peak output voltage and peak currents.